Psychological responses toward allocation of indoor plants in virtual setting among architecture students / Shahril Khairi Abdul Shukor, Suzana Said and Izham Abdul Ghani - Abdul Shukor, Shahril Khairi; Said, Suzana; Abdul Ghani, Izham (2021)
It is common for architecture students to stay in the studio for a long period of time for their design studio courses. They are psychologically vulnerable to mental stress, downturn learning performance and increasing negative emotions. Several studies have found that visual connection with nature like indoor plants can be used as part of a therapeutic therapy method in addressing stress at the workplace. The objective of this study is to determine the impact of biophilic design on the emotion of the students by placing indoor plants in their studio in a virtual environment. 30 students from the architecture programme in Polytechnic of Sultan Idris Shah (PSIS) were selected as participants. Electroencephalography (EEG) signal is collected for both scenes of virtual studio setting with and without indoor plants. Galvanic Skin Response (GSR) and Heart Rate (HR) signals are used to determine the Emotional Index (EI). Participants also answered self-report assessment to validate the psychophysiological responses. The results show that the participants tend to have positive emotions with the presence of indoor plants.